Increasing Prevalence of ESBL-Producing Multidrug Resistance Escherichia coli From Diseased Pets in Beijing, China From 2012 to 2017 - Chen, Yanyun; Liu, Zhihai; Zhang, Yaru; Zhang, Zhenbiao; Lei, Lei; Xia, Zhaofei (Frontiers in Microbiology, 2019)
We investigated antimicrobial resistance trends and characteristics of ESBL-producing Escherichia coli isolates from pets and whether this correlates with antibiotic usage in the clinic. Clinical samples containing E. coli from diseased cats and dogs were screened for antibiotic sensitivity and associated genotypic features. We identified 127 E. coli isolates from 1886 samples from dogs (n = 1565) and cats (n = 321) with the majority from urinary tract infections (n = 108, 85%). High rates of resistance were observed for β-lactams and fluoroquinolones and resistance to > 3 antibiotic classes (MDR) increased from 67% in 2012 to 75% in 2017 (P < 0.0001). This was especially true for strains resistant to 6–9 antibiotics that increased from 26.67 to 60.71%. Increased rates in β-lactam use for clinical treatment accompanied these increasing resistance rates. Accordingly, the most frequently encountered subtypes were blaCTX–M (n = 44, 34.65%), blaCTX–M–65 (n = 19) and blaCTX–M–15 (n = 18) and qnrB (n = 119, 93.70%). The blaCTX–M-isolates possessed 36 unique pulsed field electrophoretic types (PFGEs) and 28 different sequence types (STs) in ST405 (7, 15.9%), ST131 (3, 6.8%), ST73, ST101, ST372, and ST827 (2, 4.5% each) were the most prevalent. This data demonstrated a high level of diversity for the blaCTX–M-positive E. coli isolates. Additionally, blaNDM–5 was detected in three isolates (n = 3, 2.36%), comprised of two ST101 and one ST405 isolates, and mcr-1 was also observed in three colistin-resistant E. coli with three different STs (ST6316, ST405, and ST46). Our study demonstrates an increasing trend in MDR and ESBL-producing E. coli and this correlated with β-lactam antibiotic usage for treatment of these animals. This data indicates that there is significant risk for the spread of resistant bacteria from pets to humans and antibiotic use for pets should be more strictly regulated.